Pelatihan Peningkatan Kreativitas Pengolahan Makanan dan Higenitas Bagi Pedagang Makanan Di Objek Wisata Batang Arau - Afifah, Afifah; D, Ranti K.; Yanita, Novi; R, Rafidola M.; H, Alfatah (Universitas Nusantara PGRI Kediri, 2020)
Batang Arau is a newly developed tourist attraction in the city of Padang. The development of this object has an impact on the opening of opportunities to trade food for mothers who live in the area. The problem is that the food offered is still processed simply and does not pay much attention to hygiene in the processing and serving it. For this reason, training activities are carried out which aim to provide an understanding of the importance of creativity in trying primarily to process food and the importance of hygiene in the processing and serving of food. This activity also provides training on examples of processing food with fish-based ingredients that are widely available in the area. As a result traders get an understanding of the importance of creativity and hygiene in food trading and they are also able to develop ideas from food preparation examples that are trained.